2020
DOI: 10.3389/fnmol.2020.00107
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ASC Application on Endplate Regeneration Upon Glycerol-Induced Muscle Damage

Abstract: Amongst other approaches, adipose-derived stromal cells (ASCs) have recently been tested with respect to their regenerative capacity for treatment of neuromuscular disorders. While beneficial effects of ASCs on muscle recovery were observed previously, their impact on regeneration of neuromuscular junctions (NMJs) is unclear. Here, we used a murine glycerol damage model to study disruption and regeneration of NMJs and to evaluate the effects of systemic application of ASCs on muscle and NMJ recovery. In mice t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
1
2
0
Order By: Relevance
“…Glycerolinduced muscle injury significantly promoted levels of melatonin and Pax7 protein expression in TA muscle, and decreased muscle-specific differentiation markers MyHC, desmin and Pax7, as indicated by IHC staining (Figure 6I). Previous research has demonstrated that glycerol causes muscle necrosis through the loss of dystrophin protein marker expression in fibers [34]. In this study, immunofluorescent data showed that melatonin significantly reversed dystrophin protein expression in muscle fibers (Figure 6K).…”
Section: Melatonin Improves In Vivo Skeletal Muscle Dystrophysupporting
confidence: 65%
“…Glycerolinduced muscle injury significantly promoted levels of melatonin and Pax7 protein expression in TA muscle, and decreased muscle-specific differentiation markers MyHC, desmin and Pax7, as indicated by IHC staining (Figure 6I). Previous research has demonstrated that glycerol causes muscle necrosis through the loss of dystrophin protein marker expression in fibers [34]. In this study, immunofluorescent data showed that melatonin significantly reversed dystrophin protein expression in muscle fibers (Figure 6K).…”
Section: Melatonin Improves In Vivo Skeletal Muscle Dystrophysupporting
confidence: 65%
“…Accompanying data strongly support previous findings that MSCs are entrapped within the lungs, retained within the lung microvasculature, and rapidly cleared within the first one to three days ( 49 , 50 ). So far, we were only able to track MSCs within a tissue when locally applied to the tissue, e,g, skin or muscle ( 51 , 52 ). Given that we did not observe differences between i.v.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired muscle regeneration is associated with muscle injuries or myopathy [ 66 , 67 ]. Previous research has shown that glycerol injury induces early fibrosis in rat skeletal muscle [ 68 ] and disrupts neuromuscular junctions in skeletal muscle [ 69 ]. Our in vivo results revealed the rapid appearance of early-stage muscle injury after glycerol treatment.…”
Section: Discussionmentioning
confidence: 99%